Peer-led revision course of the subject "Medical psychology and sociology" for preclinical international medical students [data] - Sgrott, Julia; Nikendei, Christoph; Friederich, Hans-Christoph; Dönnhoff, Ivo (Universität, 2025)
In this study we evaluated the objective improvement of international preclinical medical students' knowledge in the subject 'Medical Psychology and Sociology' after attending a 3-day peer-led revision course. Using a pre-post-test-design, we found a significant improvement of post-results, compared to pre-results. This data verse contains our collected data as well as the R code used for statistical analysis. We also provide a RMarkdown file with our results. All participants are anonymised.
Gesehen am 14.04.2025
Keywords: Forschungsdaten; Datenbank